Co-occurrence of Point Mutations in the Voltage-Gated Sodium Channel of Pyrethroid-Resistant Aedes aegypti Populations in Myanmar - Kawada, Hitoshi; Oo, Sai Zaw Min; Thaung, Sein; Kawashima, Emiko; Maung, Yan Naung Maung; Thu, Hlaing Myat; Thant, Kyaw Zin; Minakawa, Noboru (PLOS Neglected Tropical Diseases, 2014)
Background Single amino acid substitutions in the voltage-gated sodium channel associated with pyrethroid resistance constitute one of the main causative factors of knockdown resistance in insects. The kdr gene has been observed in several mosquito species; however, point mutations in the para gene of Aedes aegypti populations in Myanmar have not been fully characterized. The aim of the present study was to determine the types and frequencies of mutations in the para gene of Aedes aegypti collected from used tires in Yangon City, Myanmar. Methodology/Principal Findings We determined high pyrethroid resistance in Aedes aegypti larvae at all collection sites in Yangon City, by using a simplified knockdown bioassay. We showed that V1016G and S989P mutations were widely distributed, with high frequencies (84.4% and 78.8%, respectively). By contrast, we were unable to detect I1011M (or I1011V) or L1014F mutations. F1534C mutations were also widely distributed, but with a lower frequency than the V1016G mutation (21.2%). High percentage of co-occurrence of the homozygous V1016G/S989P mutations was detected (65.7%). Additionally, co-occurrence of homozygous V1016G/F1534C mutations (2.9%) and homozygous V1016G/F1534C/S989P mutations (0.98%) were detected in the present study. Conclusions/Significance Pyrethroid insecticides were first used for malaria control in 1992, and have since been constantly used in Myanmar. This intensive use may explain the strong selection pressure toward Aedes aegypti, because this mosquito is generally a domestic and endophagic species with a preference for indoor breeding. Extensive use of DDT for malaria control before the use of this chemical was banned may also explain the development of pyrethroid resistance in Aedes aegypti.